Flexible Photonic Crystal Material for Multiple Anticounterfeiting Applications - Peng, Chang-Yi; Hsu, Che-Wei; Li, Ching-Wen; Wang, Po-Lin; Jeng, Chien-Chung; Chang, Cheng-Chung; Wang, Gou-Jen (ACS applied materials & interfaces, 2018)
In this study, a nanoimprinting method was introduced to fabricate polycarbonate films with transparent and flexible photonic crystal (FPC) structures. The fabricated flexible polymer films display a full-color grating because of the nanohemispherical structures on the surface. Through the Bragg diffraction formula, it was confirmed that the FPC polymer films transfer a part of the light energy to the second-order diffraction spectrum. Furthermore, the full-color grating properties can be modulated through geometric deformation because of the film’s elasticity. Additionally, anticounterfeiting features were also successfully achieved when the polymer films were either engraved with drawings and bent or patterned with fluorophores, which can be revealed under ultraviolet light. The most important aspect of this research is that the preparation of this FPC-structured polymer film is inexpensive and convenient, enabling the mass production of a new generation of smart materials.